Motivational Aspect of Organizational Culture in the Quality Management System at the Enterprise - Maksymenko, І.О.; Uzun, M.V. (Економічний вісник Донбасу, 2014)
The article is devoted to the analysis of the range of issues associated with the review of the impact of organizational culture on the effectiveness of motivational mechanism of strategic management. Describes the features of the close link in the chain of organizational culture-motivation-efficiency of the company. It is established that a high level of organizational culture is a key factor in the long-term success of the enterprise, due to the influence on motivation of labor activity of the personnel. It’s determined a dependence of the willingness of companies to implement large-scale transformations of the implementation of strategies to improve product quality from their organizational goals and values employees. It’s grounded the necessity of creation of effective, adaptive to new requirements, the mechanism of motivation of the personnel, as an important condition of effective activity of the company. The study revealed the influence of employee motivation on product quality. It is established that organizational culture unites staff motivation and strategy of the company. Authors propose a complex of directions for the formation of an effective organizational culture as a factor of motivation of the personnel in the quality management system at the enterprise.